2006
DOI: 10.1186/bf03353376
|View full text |Cite
|
Sign up to set email alerts
|

Well water level changes in Fairbanks, Alaska, due to the great Sumatra-Andaman earthquake

Abstract: The Mw 9.3 great Sumatra-Andaman earthquake of December 26, 2004 induced water level changes in Fairbanks, Alaska, at an epicentral distance of 10,800 km. Spike like water level changes followed by a step of water level rise were observed in at least four wells. We modeled the timing and magnitude of the water level rise using a combination of a linear trend and a step function. We calculated the misfit between the observed water level rises and our model by systematically shifting the timing of occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Even distant earthquakes may affect the local hydrology. For example after the 9.3 M Sumatra-Andaman 26 December 2006 earthquake an 11-min swarm of 14 local earthquakes was triggered near Mount Wrangell in Alaska at a distance of w11,000 km (West et al, 2005), affecting even the water level in ten water wells (Sil and Freymueller, 2006).…”
Section: Triggering: Seismicity and Piercementsmentioning
confidence: 99%
“…Even distant earthquakes may affect the local hydrology. For example after the 9.3 M Sumatra-Andaman 26 December 2006 earthquake an 11-min swarm of 14 local earthquakes was triggered near Mount Wrangell in Alaska at a distance of w11,000 km (West et al, 2005), affecting even the water level in ten water wells (Sil and Freymueller, 2006).…”
Section: Triggering: Seismicity and Piercementsmentioning
confidence: 99%
“…Among hydrological responses, water level changes are the most widely reported responses. Documented water level changes are typically analyzed in one of two ways: considering how one particular well responds to multiple earthquakes (Roeloffs, 1998;Weingarten and Ge, 2014;Zhang et al, 2015), or contrasting how a set of wells responds to a single earthquake (King et al, 1999;Roeloffs et al, 2003;Sil and Freymueller, 2006). Both approaches provide complementary insight into interactions between hydrogeological and tectonic processes (Manga and Wang, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many have occurred at great distances from the ruptured fault and where the associated static stress changes are relatively small (e.g., Kayen et al 2004;Sil and Freymueller 2006;Chadha et al 2008). Liu and Manga (2009) reported that significant water-level changes can be driven at great distances by moderate-amplitude dynamic (time-varying) stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2009) found that groundwater flow associated with S and Love waves may generate shear stresses large enough to break up the flocs in sediment pores, thereby enhancing the permeability of aquifers. Others have theorized that the dynamic strain induced by the passage of seismic waves, most probably long-period surface waves, might be the cause of water-level changes in the far field (West et al 2005;Sil and Freymueller 2006;Chadha et al 2008 Π). In addition, the results of several laboratory experiments suggest that dynamic shaking can enhance effective permeability, especially that of fractured systems (Roberts 2005;Elkhoury et al 2011;Candela et al 2014).…”
Section: Introductionmentioning
confidence: 99%